Impact of the Productive SafetyNet Program on the minimum acceptable diet in the rural community of South Gondar Zone, Northwest Ethiopia - Engidaw, Melaku Tadege; Gebremariam, Alemayehu Digssie; Kefale, Belayneh; Tesfa, Desalegn; Tiruneh, Sofonyas Abebaw; Shiferaw, Yalelet Fentaw (Frontiers in Sustainable Food Systems, 2023)
Background Even though numerous factors contribute to undernutrition, it can happen immediately due to poor intake and illness. A minimum acceptable diet is one of the proxy measures for adequate consumption, which is an impact indicator for the Productive SafetyNet Program (PSNP). As a result, this study aimed to assess the impact of PSNP on the minimum acceptable diet among rural infants in the South Gondar Zone, Northwest Ethiopia. Methods A community-based cross-sectional study design was employed in the selected woredas (districts) of South Gondar Zone, Northwest Ethiopia, from 1 December 2017 to 30 January 2017. A total of 442 participants' data were collected during this time period through interviews with their mothers or caregivers. A multistage sampling technique was employed to select study subjects and interviewees using a structured questionnaire. Stata version 16 (MP) was employed to carry out a statistical analysis. A binary logistic regression model was employed to identify significant variables. The statistical significance was declared at a p-value of more than 0.05. Results The highest proportion of adequate diet diversity scores (261 [59.05%]) was from households who graduated (not part of it) from PSNPs. In this study, the magnitude of adequate dietary diversity, meal frequency, and minimum acceptable diet was 79.86, 82.58, and 66.52%, respectively. Marital status (AOR = 3.98, 95% CI: 1.39, 11.40), child age (AOR = 2.82, 95% CI: 1.78, 4.47), the educational status of the father (AOR = 0.56, 95% CI: 0.35, 0.89), the wealth index (AOR = 0.27, 95% CI: 0.12, 0.64), and the place of delivery (AOR = 3.14, 95% CI: 1.47, 6.73) were significant predictors for minimum acceptable diet uptake by children. Conclusion In this study, two-thirds of the infants had/received a minimum acceptable diet. Furthermore, infants from households with Productive SafetyNet users had a low minimum acceptable diet. Marital status, the educational status of the father, child age, the wealth index, and the place of delivery were associated factors with having an adequate intake of minimum acceptable diet by the children. Therefore, efforts to address sociodemographic and child-related factors during routine care are crucial.